Finite element stress and vibration analysis of belt-pulley systems - Ching, Ngee Yeung (Nanyang Technological University, 2023)
In this FYP, a flat belt and pulley system is modelled in ANSYS Workbench. Static structural and modal analyses are carried out to find the stress distribution in the belt, as well as its natural frequencies and mode shapes under different load conditions. Firstly, a pretension is applied to the belt to analyse the stress distribution and natural frequencies of the belt. Verification of the stress results is carried out by comparing the belt tensile force distribution from Finite Element Analysis (FEA) with the force distribution derived from the Capstan equation. The prediction from the finite element model is found to follow said equation well. The coefficient of friction of the belt-pulley interface is varied to study the belt behaviour in the contact region. As the coefficient increases, the minimum belt tensile stress decreases and the maximum belt thickness increases. As the belt pretension increases, the belt natural frequencies increase as well. Secondly, a moment is applied onto the pulley to analyse the forces in a belt during operation under equilibrium conditions. The applied moment on the pulley is varied to study its effects on the belt stress distribution and its natural frequencies. As the applied moment is increased, the tight side of the belt experiences an increase in tensile stress and natural frequencies. Conversely, the slack side of the belt undergoes a reduction in tensile stress and natural frequencies. Finally, a transient analysis is carried out on the belt-pulley system to observe the “belt tracking” on crowned pulleys. It is found that during normal operation of the belt-pulley system, the belt exhibits tracking or centring behaviour when not in contact with the pulley.